Pomegranate - Lagouri, Vasiliki (IntechOpen, 2022)
Pomegranate (Punica granatum L.) is one of the oldest edible fruits in the Mediterranean and has been used extensively in folk medicine. This book summarizes the antioxidant properties and bioactive polyphenolic ingredients in Greek pomegranate varieties and the vasculoprotective and neuroprotective effect of various parts of pomegranate and its main compounds, especially hydrolysable tannins, ellagitannins, ellagic acid, and their metabolites. Research has shown that pomegranate extracts possess unusual and potent broad-spectrum activities against Gram-positive and Gram-negative bacteria, fungi, viruses, and parasites. As such, the book also explores the role of pomegranate in the treatment of cancer and SARS-CoV-2 infection. Finally, the book investigates the post-harvest management of pomegranate in industrial processing to improve pomegranate utilization for human health.